Household Economic Empowerment by the Office of Women's Empowerment and Child Protection (Study in Somba Opu Sub-District, Gowa Regency) - Yamin, Muh Nur; Assidiq, Yasir; Niswaty, Risma (Jurnal Aktor, 2024)
This study aims to determine Household Economic Empowerment by the Office of Women's Empowerment and Child Protection (Study in Somba Opu District, Gowa Regency). This research includes descriptive qualitative research with data collection techniques through observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation and conclusions. The implementation of the process and the achievement of the above empowerment objectives are achieved through the application of the empowerment approach which can be abbreviated to 5P, namely: Enablement (Potential Development), Strengthening (capability), Protection, Support (Support) and Maintenance. The results showed that Household Economic Empowerment by the Office of Women's Empowerment and Child Protection (Study in Somba Opu District, Gowa Regency) in general empowerment has been carried out quite well, but still needs to be optimized in application and innovation in empowering.